The determinants of capital structure for oil and gas company in Malaysia / Syed Afiq Syaamil Syed Khalid - Syed Khalid, Syed Afiq Syaamil (Faculty of Business and Management, 2018)
The purpose of this study is to investigate the determinants of capital structure for oil and gas company in Malaysia. The data was collected from first quarter 1996 until fourth quarter 2016. The four independent variables that had been used which are size of company (SIZE), profitability (PROF), financial strength (FIN) and company risk (RISK). This study applies Ordinary Least Square (OLS) methods in order to define the statistical relationship among the variables. There are steps involved in the research begin with ordinary least square methods and proceed with Unit Root tests, Descriptive Statistic, Multiple Linear Regressions Model and Diagnostic Tests. The results show that profitability (PROF) has a positive significant relationship while financial strength (FIN) has a negative significant relationship with capital structure of oil and gas company in Malaysia. However, size of company (SIZE) and company risk (RISK) have insignificant relationship towards capital structure of oil and gas company in Malaysia.